2008
DOI: 10.4049/jimmunol.181.7.4461
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ-Induced TNF-α Expression Is Regulated by Interferon Regulatory Factors 1 and 8 in Mouse Macrophages

Abstract: We have previously described that IFN-γ induces cyclooxygenase 2 and inducible NO synthase expression by a mechanism that involved endogenously produced TNF-α. In this study, we report that TNF-α production is induced by IFN-γ treatment in the murine macrophage cell line RAW 264.7. TNF-α mRNA levels are increased in cells treated with IFN-γ in a time-dependent manner and IFN-γ also increased human TNF-α promoter-dependent transcription. Two regions in the TNF-α promoter seem to be responsible for the IFN-γ res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(92 citation statements)
references
References 60 publications
5
84
3
Order By: Relevance
“…This indicates that IFN-g treatment results in efficient priming/amplification of TLR4-induced cellular responses. However, IFN-g alone did not induce TNF-a secretion and iNOS expression in rat aMfs, which is contrary to previous results in RAW 264.7 peritoneal macrophages cell line (36), where IFN-g upregulates TNF-a and iNOS production.…”
Section: Sp-a Inhibits Lps and Ifn-g Effects On Rat Amfscontrasting
confidence: 99%
“…This indicates that IFN-g treatment results in efficient priming/amplification of TLR4-induced cellular responses. However, IFN-g alone did not induce TNF-a secretion and iNOS expression in rat aMfs, which is contrary to previous results in RAW 264.7 peritoneal macrophages cell line (36), where IFN-g upregulates TNF-a and iNOS production.…”
Section: Sp-a Inhibits Lps and Ifn-g Effects On Rat Amfscontrasting
confidence: 99%
“…This suggests that TNF-␣ up-regulates both mTGF-␤1 and endogenous TNF-␣ expression in this cell line and that TNF-␣ may induce mTGF-␤1. It has been reported that IFN-␥ induces TNF-␣-regulated signaling by inducing TNF-␣ expression in mouse macrophages (23,24). However, in our model, IFN-␥ alone is not sufficient to induce endogenous TNF-␣ expression.…”
Section: Tnf-␣ Is Also An Inducer Of Mtgf-␤1contrasting
confidence: 65%
“…Macrophages and T cells are considered to be the main source of TNF-a. Production of TNF-a in macrophages is regulated by TLR via activation of NF-kB and by IFN-g via activation of IFN regulatory factors during infection (23,24). The production of TNF-a in Th1 cells is transcriptionally regulated by T-bet (25,26).…”
Section: Discussionmentioning
confidence: 99%